Ozone Generation Via DBD Plasma for Water and Curd Treatment - Dhami, Janak Singh; Jyakhwo, Sunil; Thapa, Bhesh Bahadur; Tyata, Raju Bhai (Journal of Science and Engineering, 2025)
Dielectric Barrier Discharge (DBD) plasma technology offers a sustainable approach to ozone (O_3) generation for environmental and food safety applications. In this study, a coaxial DBD reactor operating at atmospheric pressure with applied voltages of 2–12 kV and an airflow rate of 10 L/min was utilized to generate ozone for treating contaminated river water, well water, and curd. Ozone quantification via iodometric titration revealed that dissolved ozone concentration increased with treatment duration, reaching saturation at 0.9 mL of sodium thiosulfate after 7 minutes, corresponding to a 5.2 mg/L ozone concentration. Microbial analysis using the Most Probable Number (MPN) method demonstrated complete elimination of bacterial contamination in ozone-treated samples, with untreated controls showing persistent growth across all replicates (e.g., untreated river water: 18/18 positive tubes; ozone-treated: 0/18). Sensory evaluation of curd indicated that ozone-treated samples retained freshness for 48 hours, while untreated samples developed sourness due to unchecked lactic acid bacteria activity. These results underscore DBD plasma’s efficacy in generating ozone capable of 100% microbial inactivation in water and dairy products, positioning it as a viable chemical-free alternative for disinfection and preservation. The saturation kinetics observed suggest optimized treatment durations of 7–10 minutes for practical applications, balancing energy efficiency and efficacy.